QIRA`AH MU`ASIRAH: REVOLUSI METODE PENAFSIRAN AL QURAN MUHAMMAD SYAHRUR - Alfi Julizun Azwar; Muhammad Arpah Nurhayat; Ida Novita (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2019)
Tafsir bi ar-riwayat constructs the understanding of verses by using other verses related to or using hadith, qaulu asshahabah and even qaul at-tabi`in is believed by some interpreters as the correct and safe method, for them this is called the al-ashil interpretation which accepted because of having source while the interpretation that ignores these aspects is called the ad-dakhil interpretation which is rejected, another case with Muhammad Syahrur who actually invites to disconnect the verse with each context. In other words the verse stands alone and its words is a great miracle owned by the Koran he named this project the term Qiraah mu`ashashirah with two approaches which he called tanasuq al-ayah bil-ayah and nadhariyyatul hudud.